TEACHING STYLES, MOTOR SKILLS AND SPRINTING SKILLS LEARNING OUTCOMES - Akhmad Sobarna (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this study was to look for the effectiveness of teaching styles on learning outcomes seen sprinting skills of motor skills. The method used is experiment with a 2x3 factorial design treatment. Population research is College of teacher training and education students that amounted to 12 classes, conten 360 person. The sample was selected using simple random sampling. The study was conducted during one month with 16 times meeting. Research instrument using sprint test and rubric. The results of the study concluded that: (1) There are differences in skill scamper between teaching style inclusion, training and reciprocal as a whole, (2) There are differences in skill scamper between motor skills and high motor abilities low overall, (3) There is an interaction between style teaching and motor skills against the skills to sprint overall. Keywords: Teaching Style, motor skills, sprint